A Bacterial Evaluation Of Tonsillitis In Baghdad - AD'hlah, A. H; AL-Abdulwahed, L. S. A; ALkashaly, S. S. A (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A sample  of  168 tonsillitic  subjects  (93  males and  75 females), livin g in Baghdad was evaluated  microbiologically.   The patients  had an age  range  of  3-35  years.          Four  bacterial   species  were   isolated  and identified.    They             were              P-haemolyt ic Streptococcus    ,(39.3%) Staphylococcus                                 aureus,(23.8% )Haemophilus                          injluenzae (20.8% )and a-haemolytic Streptococcus.  (16.1 %)Sex differences  in the prevalency of these   bacteria   were   observed.   Lancefield   grouping   of P-haemolytic Streptococcus showed  five  sera-groups  (A,  B, D,  G  and  Non-typable). The  A  group  dominated   the  list  (72.7%),  followed   by  the  B  group (13.6%), while the others shared a similar frequency (4.5% ).